2007
DOI: 10.1080/08977190701783400
|View full text |Cite
|
Sign up to set email alerts
|

In vitroculture of testicular germ cells: Regulatory factors and limitations

Abstract: Spermatogenesis is regulated mainly by endocrine factors and also by testicular paracrine/autocrine growth factors. These factors are produced by Sertoli cells, germ cells, peritubular cells and interstitial cells, mainly Leydig cells and macrophages. The interactions and the ratio between Sertoli and germ cells in the seminiferous tubules ensure successful spermatogenesis. In order to culture spermatogonial stem cells (SSCs) in vitro, researchers tried to overcome some of the obstacles -- such as the low numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 157 publications
0
60
0
1
Order By: Relevance
“…Interestingly, coculture of PS with SCs significantly augmented the hyperthermia-induced YES1 activation during early recovery. In support of this observation, accumulated evidence has shown that SCs synthesize and secrete approximately 60 various proteins, among which many are known to act as general and/or tissue-specific survival factors (e.g., epidermal growth factor [EGF] and stem cell factor [SCF]) [41][42][43]. Furthermore, large volumes of data are indicative of an antiapoptotic effect of SC-GC interaction.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, coculture of PS with SCs significantly augmented the hyperthermia-induced YES1 activation during early recovery. In support of this observation, accumulated evidence has shown that SCs synthesize and secrete approximately 60 various proteins, among which many are known to act as general and/or tissue-specific survival factors (e.g., epidermal growth factor [EGF] and stem cell factor [SCF]) [41][42][43]. Furthermore, large volumes of data are indicative of an antiapoptotic effect of SC-GC interaction.…”
Section: Discussionmentioning
confidence: 79%
“…Without this factor, either spermatogonial aggregates do not develop or SSCs perish. 15 The generation process of SSCs and spermatogonia 9,16,17 and also the localization of undifferentiated spermatogonia along specific portions of the basement membrane are done via stimuli from the vascular network and interstitial cells, ie, the peritubular myoid cells and the Leydig cells. 18 On the other hand, the adhesion molecules of the basement membrane are anchored with SSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the growth factors, GDNF (Glial-Cell-Line-Derived Neurotrophic Factor) is the most crucial factor to promote SSC self-renewal leading to a balance set between SSCs self-renewal and differentiation [47][48][49]. Without GDNF, spermatogonial aggregation cannot occur or SSCs may be perished [50]. In the cell culture, we experienced increased number of SSCs via self-renewal in presence of GDNF and somatic cells.…”
Section: Discussionmentioning
confidence: 96%